As percepções e contribuições dos residentes sobre a formação inicial docente a partir do Programa Residência Pedagógica - Silva, Marcos Paulo (Universidade Federal de São Carlos, 2023)
This work sought to analyze the experience reports of students at the degree course in Chemistry from the Pedagogical Residency Program at Araras campus of UFSCar, during the notice in force between the years 2020 and 2022, in the context of the COVID-19 pandemic, during this period there was a suspension of face-to-face classes, making it necessary to adopt remote teaching in schools and universities as one of the measures to mitigate the spread of the virus responsible for the disease. Analyze the consequences of remote teaching for students of basic and university education, within the scope of the Program and mandatory supervised internships, is essential to analyze the initial teacher training in the remote context. In this way, the work aimed to analyze the contributions of PRP in their initial training as teachers in context of remote teaching. To analyze the experience reports, the Discursive Textual Analysis and, through it, the categorization was carried out and, finally, the construction of a reflective metatext. At the end of document analysis, the contribution of the Program to the residents was noted and also some limitations faced in presenting the selected themes in the context remote. Another highlight was the work carried out in such a between undergraduate students and also the heterogeneity between classes, factors these were positive for the initial training of undergraduates.
Residents' perceptions and contributions about initial teacher training from the Pedagogical Residency Program
Keywords: Programa de Residência Pedagógica; Formação de professores; Teacher training; PRP; Ensino remoto; Remote teaching; Pandemia; Pandemic; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO